2003
DOI: 10.1029/2002jd002899
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seasonality, canopy light extinction, and terrain on potential isoprenoid emission from a Mediterranean‐type ecosystem in France

Abstract: [1] Sensitivity studies for simulations of yearly cycles and terrain effects are presented for the St.-Martin-de-Londres region (southern France). Potential isoprenoid emissions are simulated using the Solar Radiation Model (SORAM), spatial effects of complex terrain, photosynthetically active radiation, and surface temperature. SORAM is embedded in a geographic information system (GIS) environment and considers a digital elevation model (DEM) of the model domain. Compared to the maximum case (i.e., no variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The length of this lag phase depends on the growth temperature and may exceed ten days (Wiberley et al, 2005). For senescing leaves, a decline in emission capacity has been found (Monson et al, 1994;Schaab et al, 2003). Some global models account for this effect, either by assigning younger and older leaves lower emission capacities Lathière et al, 2006), or modelling emission capacity in deciduous trees as a function of growing degree day temperature sums (Arneth et al, 2007b).…”
Section: Leaf Developmental Stagementioning
confidence: 99%
See 3 more Smart Citations
“…The length of this lag phase depends on the growth temperature and may exceed ten days (Wiberley et al, 2005). For senescing leaves, a decline in emission capacity has been found (Monson et al, 1994;Schaab et al, 2003). Some global models account for this effect, either by assigning younger and older leaves lower emission capacities Lathière et al, 2006), or modelling emission capacity in deciduous trees as a function of growing degree day temperature sums (Arneth et al, 2007b).…”
Section: Leaf Developmental Stagementioning
confidence: 99%
“…A number of previous studies have shown that clear-sky space-borne formaldehyde (HCHO) columns can be used to quantitatively test current understanding of isoprene emissions on regional to continental spatial scales (e.g., Chance et al, 2000;Palmer et al, 2001;Palmer et al, 2003;Shim et al, 2005;Abbot et al, 2003). Most of these studies have used HCHO column data from GOME or -more recently-from the newer Ozone Monitoring Instrument (OMI) space-borne sensor aboard the NASA Aura satellite (Millet et al, 2006).…”
Section: Top-down Constraints For Emission Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This requires the coupling of an emission model with a process-based SVAT (soil-vegetation-atmosphere transfer) model. Such models describe leaf scale processes, set the micrometeorological canopy conditions which drive these processes, and describe the biomass and foliage distribution throughout the canopy (Baldocchi et al, 1999;Grote, 2006;Lamb et al, 1993;Lenz et al, 1997;Schaab et al, 2003). Such an approach also requires reliable information of emission potentials of each individual species.…”
Section: Introductionmentioning
confidence: 99%